การศึกษาสมรรถนะของพยาบาลเวชปฏิบัติทางตา - จินตนา ไพบูลย์ธนานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this research was to study of ophthalmic nurse practitioner competencies by using Ethnographic Delphi Future Research Technique (EDFR). The 20 experts were ophthalmologists, committee members of Continuing Nursing Education Nursing Council Thailand, instructor of ophthalmic nurse practitioners and ophthalmic nurse practitioners. The EDFR consisted of 3 steps. Step 1: All experts were asked for describing ophthalmic nurse practitioner competencies. Step 2: study data were analyzed by using content analysis and then developed questionnaire. All items in the questionnaire were ranked competencies{174} level by previous experts. Step 3: those items were analyzed by using mean and Interquatile range and then developed a new questionnair sent to experts again for items{174} ranking confirmation. Those items were analyzed by using mean and Interquatile range and then summarized the overall of ophthalmic nurse practitioner competencies. The results revealed that ophthalmic nurse practitioner competencies composed of 86 items. Most of them,78 items, were evaluated as the most essential competencies and the rest were indicated as essential competencies. All competencies items could be classified into 2 groups 8 dimensions as follows: 1. specific competencies 2 dimensions: 1)Nursing care 11 items. 2)Advanced Ophthalmic nursing practitioners 18 items. 2. general competencies 6 dimensions: 1)Consulting 9 items. 2)Doing research 6 items. 3)Leadership 11 items. 4)Ethics and Integrity 7 items. 5)Nursing administrative 15 items. 6)Using Technology 9 items.